EFFECTS OF ELEVATED TEMPERATURE ON COMPRESSIVE STRENGTH OF CONCRETE: A CASE STUDY OF GRADE 40 CONCRETE (Nigerian Journal of Technology, 2015)
This study presents the results of investigation of the effects of elevated temperatures on the compressive strength of Grade 40 concrete. A total of thirty cube specimens were cast, cured in water at ambient temperature in the laboratory and subjected to various temperature regimes before testing. A concrete mix of 1:1:3 (cement: fine aggregates: coarse aggregates) with water content ratio of 0.44, fine aggregates lying in zone 2 of sieve tests as well as granite of maximum size 12.5mmwas designed for these investigations using the Department of Environment Method. Specimens cured for 7 and 28 days were subjected to uniaxial compressive loading tests at room and elevated temperature of 24, 100, 150, 200, 250 and 300 degree Celsius at one hour duration. The result indicated 14.49%, 25%, 51%, 35.51% and 43.88% decrease in compressive strength at the earlier quoted temperatures respectively. At an elevated temperature of 300 degrees Celsius a peak decrease of 53.47% in compressive strength was observed. http://dx.doi.org/10.4314/njt.v34i3.7